SCAR Marker for Gender Identification in Date Palm (Phoenix dactylifera L.) at the Seedling Stage. (17th October 2018) - Al-Qurainy, Fahad; Al-Ameri, Abdulhafed A.; Khan, Salim; Nadeem, Mohammad; Gaafar, Abdel-Rhman Z.; Tarroum, Mohamed
Abstract : Date palm ( Phoenix dactylifera L.) is cultivated in arid and semiarid regions worldwide. Given the dioecious nature of this plant, gender identification is very important at the seedling stage. Molecular markers are very effective tools that help in gender identification at this stage. A sequence characterized amplified region (SCAR) marker linked to sex-specific regions in the genome of date palm was developed. Of the 300 tested randomly amplified polymorphic DNA (RAPD) primers, only one primer (OPC-06) produced reproducible band (294 bp) in male plants. The PCR product of this primer was cloned and sequenced. The specific primers were synthesized for amplification of a 186 bp fragment in male date palm plants. These primers were validated in male and female date palm plants, wherein the designed SCAR marker was reported only in male plants and no amplification was observed in female plants. The developed SCAR marker was used with seedlings of date palm and proved very effective in identification of gender.